(3TQM YbGFO GdfSajs - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J(B793(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; hHg fSJYjf GdMeO ddg GdeJhMO HLdGd PGJg hceGd UaGJg GdeJbOS aj fYhJ GdLHQhJ Yf ThGjH GdfbU hSeGJg hGdUdGI Ydi fHjg eMeO GdeDjO HSGWY MLLg hhGVM HjfGJgs
(3BNQgG (B:s
(3aGdJQbj hGdYdh EfeG gh aj CeQ GdJLQO hEXgGQ GdBKGQ GdbhjI dG aj eWdb GdTQa hGdceGd adG OdGdI Ydi CaVdjI GdedGFcIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 219s
(3eYLe GdeDdajf (B3 / 849s
(3cTa GdXfhf (B2 / 1145s
(3TPQGJ GdPgH (B6 / 309s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds